#1**+1 **

Solve for x:

(log(x))/(log(2)) + (log(3))/(log(2)) = 1 + (log(9))/(log(2))

Rewrite the left hand side by combining fractions. (log(x))/(log(2)) + (log(3))/(log(2)) = (log(x) + log(3))/(log(2)):

(log(x) + log(3))/(log(2)) = 1 + (log(9))/(log(2))

Multiply both sides by log(2):

log(x) + log(3) = log(2) + log(9)

Subtract log(3) from both sides:

log(x) = log(2) - log(3) + log(9)

log(2) - log(3) + log(9) = log(2) + log(1/3) + log(9) = log(2) + log(1/3) + log(9) = log((2 9)/3) = log(6):

log(x) = log(6)

Cancel logarithms by taking exp of both sides:

**x = 6**

Guest Nov 3, 2017